Perencanaan dan Implementasi Penggunaan Keran Wastafel Otomatis Berbasis Mikrokontroler Arduino Uno dalam Penanggulangan Pencegahan Covid-19 pada Pasar Tradisional Desa Suka Maju: Perencanaan dan Implementasi Penggunaan Keran Wastafel Otomatis Berbasis Mikrokontroler Arduino Uno dalam Penanggulangan Pencegahan Covid-19 pada Pasar Tradisional Desa Suka Maju - Yudi Chandra; Erick Radwitya; Sy. Ishak Alkadrie (Pengelola Jurnal Politeknik Negeri Ketapang, 2021)
Community service is one of the pillars of the Tri Dharma of Higher Education, in addition to the Dharma of Education and Teaching and the Dharma of Research. This time, the Ketapang Polytechnic Community Service Program aims to apply knowledge that can be used by the public in the prevention of the spread of Covid-19 which can be contagious in crowded places. Covid-19 is a virus that is easily transmitted through human touch and from human beings to human beings, and it can be said that the Covid-19 virus is easily transmitted in crowded places in the community. One of the most crowded places in the community is the traditional market, which is still active, namely the traditional BUM Desa Karya Maju market which is located on the Poros Sukadana-Ketapang road, Muara Pawan District, Suka Maju Village. Through the Community Service Program the initiative to make a tool that can overcome the prevention of the spread of covid-19. One method of preventing Covid-19 is to always wash your hands after touching so as to make an automatic sink faucet based on the Arduino UNO microcontroller. The tools that are made can be moved according to the expectations of the partners. The components of the tool are the seat frame, barrel, sink, wheels and control components. The control components consist of an adapter, charger module, battery, switch, Arduino UNO module, relay module, ultrasonic sensor and PMPA DC.